Faktor yang Memengaruhi Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Denpasar Utara - Riyatna, Kadek Danu Dwika; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
Accountability is the responsibility of the village government regarding the management of village funds to the community in a transparent, honest, orderly and disciplined manner. The purpose of providing village funds is in line with Law no. 6 of 2014 which is to improve the welfare of the community. This study aims to determine the effect of village head leadership, village apparatus competence and community participation on fund management accountability in 8 villages in North Denpasar District with 178 respondents. Data collection by using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that the leadership of the village head and the competence of the village apparatus had a positive influence on the accountability of village fund management in North Denpasar District, while community participation had no significant effect on the accountability of village fund management in North Denpasar District. Keywords : Accountability; Leadership; Competence; And Community Participation.